Ethnopyramid Terintegrasi Rumah Adat Limas Potong Batam Sebagai Pendukung Literasi Numerasi Siswa Berbasis Android (Universitas Dr. Soetomo, 2024)
The PISA study in 2022 showed that the score of numeracy literacy skills in Indonesia is still relatively low despite the increase in rank, this is caused by various factors such as a lack of numeracy literacy and less innovative learning. To improve students' numeracy literacy skills, this development research was conducted to develop an Augmented Reality (AR) assisted learning media integrated by the ‘Limas Potong’ traditional house in Batam to support students' numeracy literacy skills in class VIII geometry material. The research and development (R&D) method used is the ADDIE model focusing on three stages, namely analysis, design, and development. Product validation was reviewed from material aspects, question aspects, language aspects, implementation aspects, software engineering aspects, and visual communication aspects. The results of the product validity test conducted by several experts obtained an average score of 3.53 (very valid), indicating that the results of the development of Augmented Reality (AR) applications named